2002
DOI: 10.1007/s00520-001-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone treatment in patients with brain metastases and primary brain tumors: do the benefits outweigh the side-effects?

Abstract: In order to minimize neurological symptoms and treatment-related side-effects, patients with primary or secondary brain tumors receive dexamethasone. The goal of this study was to analyze dosage and duration of dexamethasone intake and to compare the advantages and disadvantages of this medication during the course of radiation therapy (RT). Data from 138 consecutive patients were therefore analyzed retrospectively. During the course of therapy, the dosage of dexamethasone was evaluated, as were the indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
3
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 19 publications
5
130
3
4
Order By: Relevance
“…It is important to remember, however, that dose and time are important factors in treating patients with advanced cancer. The administration of high doses of dexamethasone over a long period may not be practical because of the high frequency of adverse effects [56]. Furthermore, follow-up data for patients with advanced cancer are limited because of disease progression, and logistic issues are frequent problems in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember, however, that dose and time are important factors in treating patients with advanced cancer. The administration of high doses of dexamethasone over a long period may not be practical because of the high frequency of adverse effects [56]. Furthermore, follow-up data for patients with advanced cancer are limited because of disease progression, and logistic issues are frequent problems in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone was the most commonly used steroid, and doses in four studies ranged from 8 mg to 16 mg daily; one study reported the use of prednisone at 40 mg daily 7 . In a study reporting the results of two consecutive randomized trials involving 96 patients with brain metastases, Vecht et al 3 Retrospective studies and reviews report that the most common starting dose of dexamethasone ranges between 8 mg and 16 mg daily 5,6,8,12 . In a recent review of the role of steroids in the management of brain metastases, Ryken and colleagues concluded that symptomatic patients should be treated with a starting dose of 4-8 mg daily; if the patient exhibits severe symptoms associated with increased intracranial pressure, a dose of 16 mg daily or higher could be considered 9 .…”
Section: Question 2: Dosingmentioning
confidence: 99%
“…Hyperglycemia has been reported in up to 72% of patients with primary brain tumours receiving dexamethasone 6 and might be associated with shorter survival in those patients 39,40 . The hyperglycemia from corticosteroid therapy usually occurs in the first 6 weeks of therapy and is believed to be secondary to insulin resistance and increased hepatic gluconeogenesis 24 .…”
Section: Question 4: Management Of Adverse Events Associated With Dexmentioning
confidence: 99%
“…Hempen et al 31 studied 138 patients with primary or metastatic brain tumors treated with radiation therapy. Ninety-one patients with brain metastases were treated with standard-fraction whole-brain radiation therapy for 2-3 ACR APPROPRIATENESS CRITERIA â weeks.…”
Section: Steroidsmentioning
confidence: 99%